2009
DOI: 10.1126/science.1167324
|View full text |Cite
|
Sign up to set email alerts
|

Auxin-Dependent Patterning and Gamete Specification in the Arabidopsis Female Gametophyte

Abstract: The female reproductive unit of flowering plants, the haploid female gametophyte, is highly reduced relative to other land plants. We show that patterning of the Arabidopsis female gametophyte depends on an asymmetric distribution of the hormone auxin during its syncitial development. Furthermore, this auxin gradient is correlated with location-specific auxin biosynthesis, rather than auxin efflux that directs patterning in the diploid sporophytic tissues comprising the rest of the plant. Manipulation of auxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
280
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(292 citation statements)
references
References 30 publications
10
280
2
Order By: Relevance
“…On account of its differential distribution within plant tissues, it acts as a versatile coordinative signal mediating a multitude of processes, including female gametophyte patterning, embryogenesis, organogenesis, meristem activity, growth responses to environmental stimuli and others [7][8][9][10] . High auxin concentration in germinating pollen and active auxin responses in developing pollen [11][12][13] implicated auxin also in male gametophyte development and function, but its role there remained elusive.…”
mentioning
confidence: 99%
“…On account of its differential distribution within plant tissues, it acts as a versatile coordinative signal mediating a multitude of processes, including female gametophyte patterning, embryogenesis, organogenesis, meristem activity, growth responses to environmental stimuli and others [7][8][9][10] . High auxin concentration in germinating pollen and active auxin responses in developing pollen [11][12][13] implicated auxin also in male gametophyte development and function, but its role there remained elusive.…”
mentioning
confidence: 99%
“…This polarity in the embryo sac is due to a gradient of the natural auxin indole-acetic acid along the micropyle-chalaza axis whose expression starts at the micropylar region outside of the embryo sac. In the same manner and following this pattern, the haploid egg cell which after its fertilization produces the embryo, is also highly polarized with its nucleus located at the chalazal pole (Pagnussat et al, 2009). Pagnussat et al (2009) reported that it is possible that auxin does not regulate the position of the nuclei during the embryo sac formation, however it participates in the regulation of cell fate at cellularization.…”
Section: Zygotic Embryogenesismentioning
confidence: 91%
“…In the same manner and following this pattern, the haploid egg cell which after its fertilization produces the embryo, is also highly polarized with its nucleus located at the chalazal pole (Pagnussat et al, 2009). Pagnussat et al (2009) reported that it is possible that auxin does not regulate the position of the nuclei during the embryo sac formation, however it participates in the regulation of cell fate at cellularization. After fertilization, the resulting diploid zygote remains highly polarized, while the other male gamete fuses with the central cell of the embryo sac which then develops into the triploid endosperm, acting as a nutritive and protective element for the embryo.…”
Section: Zygotic Embryogenesismentioning
confidence: 91%
“…The cellularization and differentiation of cells in the embryo sac appear to be transcriptionally regulated (Rabiger and Drews, 2013), and mechanisms involving RNA splicing and auxin and peptide signaling specify female gametic cells (Gross-Hardt et al, 2007;Pagnussat et al, 2009;Lieber et al, 2011;Lituiev et al, 2013). For male germline development, a regulatory framework for cell cycle progression and gamete specification has been established Borg and Twell, 2010;Twell, 2011).…”
Section: Introductionmentioning
confidence: 99%